(untitled) (Research, Society and Development, 2021)
Climate change has become an important issue in national and international scenarios since the 1970s. Thus, several events were organized to discuss environmental issues, in all their contexts, with a succession of multilateral negotiations that prioritized the commitment to sustainability. In 2015, the 17 Sustainable Development Goals (SDGs) were approved, with 169 targets, as part of the 2030 Agenda. In this study, SDG 6 stands out, with eight objectives related to the importance of ensuring the availability and sustainable management of water and sanitation for all. In this perspective, the objective of the work was to characterize the main international events on climate change and global responsibility and to discuss the implementation of the goals of SDG 6 in Brazil. For that, the systematic method was used, with bibliographic, normative and documentary investigations. It was found that the issue of water is permanently included in government agendas, since water is an essential resource for the maintenance of life, health and human activities. In Brazil, it can be inferred that despite the partial implementation of the goals of SDG 6, there are still many gaps and challenges for their full implementation.